THU0735-HPR Shared care of rheumatologist and nurse consultations in follow up of rheumatoid arthritis and spondyloarthritis outpatients with low disease activity: a monocentric, randomized controlled trial. (15th June 2017) - Claes, K; Hecke, A Van; Jacques, P
Abstract : Background: Due to national regulations, the role of nurses in the management of arthritis patients differs significantly in all European countries (1). In Belgium, regularized consultations conducted by a rheumatology nurse do not exist. Objectives: The study investigated whether rheumatology nurse consultations alternating with rheumatologist consultations for RA or AS patients with low disease activity is non-inferior compared to the usual care by the rheumatologist. Primary outcomes were safety and disease activity. Secondary outcomes were fatigue, pain, functional index, patient satisfaction, the level of self-management and self-efficacy. Methods: This is a monocentric randomized controlled trial. The intervention group received a consultation conducted by a rheumatologist alternating with a nurse consultation, every 8 weeks. Patients in the control group received usual care: consultations performed by a rheumatologist every 8 weeks. Results: Mixed method analyzes were performed. No statistical significant between-group effects were found nor in the RA group nor in the AS group, although there was a clinical relevance towards disease activity by AS patient in the intervention group. DAS 28 dropped with a mean difference of 0, 4 (-1, 1 – -0, 2, SD 0, 30). The ASDAS and BASDAI both decreased with 1.1 (-1, 4 – -1, 3, SD 0, 1 and -1, 7 – -1, 4, SD 0, 1 respectively). No safety signals from biochemical parameters such as SGOT, GOT and creatinine were detected. Inflammatory markers (ESR and CRP) remained stable in both groups. The secondary outcomes showed no significant between-group effects for both diseases. The self-efficacy outcome noticed a positive in-between-group effect by patients with RA in the intervention group. Conclusions: In the follow-up of patients with RA or AS and low disease activity, outcome is not different when rheumatology nurse consultations alternating with rheumatologist consultations are compared to usual care. Implementing nurse consultations can positively influence the disease activity and patient self-efficacy. References: van Eijk-Hustings Y et al. (2014) EULAR recommendations for the role of the nurse in the management of chronic inflammatory arthritis. Annals of Rheumatic Diseases 73:429–509. Disclosure of Interest: None declared